Grafts of porcine small intestinal submucosa seeded with cultured homologous smooth muscle cells for bladder repair in dogs - Rossetto, Victor J. V. [UNESP]; Mota, Ligia S. L. S. da [UNESP]; Rocha, Noeme Sousa [UNESP]; Miot, Helio A. [UNESP]; Grandi, Fabrizio [UNESP]; Brandão, Claudia Valeria Seullner [UNESP] (Biomed Central Ltd., 2013)
Background: Due to numerous complications associated to gastrointestinal augmented cystoplasty, this study aimed to analyze the anatomic repair of the bladder of 10 female dogs using grafts of porcine small intestinal submucosa (SIS) seeded with cultured homologous smooth muscle cells, and compare them with the acellular SIS grafts.Results: We assessed the possible side effects and complications of each type of graft by clinical examination, abdominal ultrasound and laboratory findings. Anatomic repair of neoformed bladder was assessed by histological staining for H/E and Masson's Trichrome, analyzed with a Nikon Photomicroscope connected to the system of image analysis Image J.Conclusions: We propose that SIS associated to homologous smooth cells can improve the quality of tissue repair, and consequently decrease the potential complications inherent to acellular SIS.
Keywords: Tissue reconstruction; Bioengineered tissue; Cell therapy; SIS